THE ANALYTICAL COMPARISON OF THE RUSSIAN FEDERATION SUBJECTS REPRESENTATIVE BODIES FORMATION CRITERIA - Oksana Sergeevna Morozova (Современная наука и инновации, 2022)
The current paper considers the domestic legislation with a purpose to analyze the requirements established for a number of deputies of the state power legislative (representative) body of the Russian Federation subjects. The article shows the pros and cons of increasing the number of deputies working on a professional basis.